2006
DOI: 10.1037/0012-1649.42.2.366
|View full text |Cite
|
Sign up to set email alerts
|

A developmental contextual perspective on identity construction in emerging adulthood: Change dynamics in commitment formation and commitment evaluation.

Abstract: A developmental contextual test of a dual-cycle model of identity formation is presented. In addition to a commitment-formation cycle-represented by Marcia's (1966) classical dimensions of exploration in breadth and commitment making--the model comprises a commitment-evaluation cycle--constituted by 2 additional dimensions of exploration in depth and identification with commitment. In a sample of 402 college students assessed 4 times over 2 years, both dimensions of the commitment-formation cycle and explorati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
292
3
13

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 335 publications
(327 citation statements)
references
References 49 publications
19
292
3
13
Order By: Relevance
“…Most freshmen can no longer rely fully on their existing network of friends and family and have to deal with many life changes and choices. Consequently, identity redefinitions are common in college students (Luyckx, Goossens, & Soenens, 2006), potentially leading to increases in life purpose and, hence, the SOC component of meaningfulness for some individuals. However, the increase in life possibilities and outcomes characteristic for college life can render this period in life more difficult to navigate as compared to the more structured life of high school (Arnett, 2000), potentially resulting in lowered feelings of the SOC components of comprehensibility and/or manageability for some individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Most freshmen can no longer rely fully on their existing network of friends and family and have to deal with many life changes and choices. Consequently, identity redefinitions are common in college students (Luyckx, Goossens, & Soenens, 2006), potentially leading to increases in life purpose and, hence, the SOC component of meaningfulness for some individuals. However, the increase in life possibilities and outcomes characteristic for college life can render this period in life more difficult to navigate as compared to the more structured life of high school (Arnett, 2000), potentially resulting in lowered feelings of the SOC components of comprehensibility and/or manageability for some individuals.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that among psychological resources, the development of the more statelike components seems the most likely to be affected by the other resources. However, the longitudinal study by Luyckx, Soenens, and Goossens (2006) indicates a dynamic interplay of trait personality characteristics and identity development among emerging adult women, suggesting that even trait-like psychological resources can be developed and affected by other resources.…”
Section: The Relationship Between the Four Career Resourcesmentioning
confidence: 99%
“…This assumption seems to be indirectly confirmed by the results of studies (Rękosiewicz, 2013a -this issue) of the relationship between identity in Luyckx's understanding (see Luyckx, Goossens and Soenens, 2006) and social participation. One of the dimensions of identity -ruminative exploration, defined as a manifestation of personal fears and experienced by a person who has problems with engagement Brought to you by | MIT Libraries Authenticated Download Date | 5/13/18 4:56 AM in issues that are important for identity development (Luyckx et al, 2008), was found to have a weak positive correlation with moratorium orientation (ruminative exploration correlated negatively with transitive orientation).…”
Section: Problemmentioning
confidence: 63%